La Inclusión Educativa Y Su Incidencia En La Autoestima De Los Niños Con Hiperactividad Del Instituto De Integración José Martí De La Ciudad De Quito. Período 2012-2013 - Villacis Hidalgo, Eliza Fernanda (2013)
This research entitled "INCLUSIVE EDUCATION AND ITS IMPACT ON THE SELF-ESTEEM OF CHILDREN WITH HYPERACTIVITY AT THE INTEGRATION INSTITUTE “JOSÉ MARTI” QUITO CITY 2012-2013”, has the general objective to determine the incidence of Inclusive Education on the self-esteem of children with Hyperactivity at the Integration Institute "José Marti.” The methods used in this research are: Scientific, Inductive, Synthetic, Analytical and Statistical. The instruments for data collection of this research consisted of a survey of fourteen parents, teen teachers and therapists to meet curricular adaptations they make to children and the Coopersmith test to determine levels of self-esteem applied to four girls teen boys and the institution. From these results we conclude that curriculum adaptations are applied 40% to avoid distracting the children sitting in the front row away from windows, 20% extends the time for completion of homework and dosed undertake homework, 10% determining fundamental objectives prioritizing the homework contents and establishes visual contact to hold the attention of children. The Coopersmith test shows that 50% of children have an average level of self-esteem, 43% a low level of self-esteem and 7% high.